SUITABILITY OF TUNA RED MEAT FOR PREPARATION OF WATERS - THANKAMMA, R; NAIR, A LEKSHMY; SHENOY, A VASANTH; GOPAKUMAR, K (Fishery Technology, 2017)
Studies to find out the suitability of tuna red meat for preparation of wafers have indicated that the red meat as such is not a good raw material for the production of wafers. The wafers obtained had poor organo]eptic quality and characteristic tuna red meat flavour unacceptable to consumers. Attempts to prepare the wafers with the red meat mixed with the meat of barracuda in varying proportions showed that the mixture of red meat and barracuda meat in the ratio 1:3 gives a product having excellent physical properties and good swelling characteristics. The overall organoleptic quality of these wafers was very much comparable to the wafers produced from other quality fish. Increasing the proportion of red meat not only affects the overall appearance of the product but a1so imparts the red meat taste to the product.